Case Detection Rates of Leprosy Disease (Lepray) In Kalimantan Selatan - Yulfida, Zahra; Paga, Zaskia Raudatul Hikma; Yakin, Siti Ainul; Zara, Wa Ode Siti; Hawaryun, Waode (Journal of Epidemiology and Health Science, 2026)
Background: Leprosy, also known as Hansen’s disease, is a chronic infectious disease caused by Mycobacterium leprae, affecting the skin, peripheral nerves, mucous membranes of the upper respiratory tract, and eyes. Although South Kalimantan Province achieved leprosy elimination status in 2021, defined by a prevalence of less than 1 per 10.000 population, new cases have continued to be reported through 2023. Objective: This study aims to assess the incidence of new leprosy cases in South Kalimantan in 2023 and to examine trends in recent years. Methods: A quantitative descriptive approach was employed using secondary data obtained from the 2023 Health Profiles of districts and municipalities across South Kalimantan. Results: The findings indicate that the incidence of new cases in 2023 was 1.8 per 100.000 population, representing a decline from 3.5 per 100.000 population in 2022. By sex, the incidence rate was higher among males (4.8 per 100.000 population) compared to females (2.1 per 100.000 population). Conclusion: Despite the observed decline, sustained efforts to strengthen early case detection, enhance active surveillance, and improve access to health services remain essential to maintain elimination status and prevent disability associated with leprosy. Keywords: Leprosy, South Kalimantan, incidence rate, early detection, elimination.